^{Solve algebraically : 3x^2/2=2(x-1)}
The first step would be to get rid of any denominators, so multiply both sides of the equation by 2 (what you do to one side of an equation you need to do to the other to maintain equality).
2*(3x^2)/2 = 2*(2(x-1)) and you get 3x^2 = 4(x-1)
Now get rid of the parentheses by distributing the 4 across the x-1 and you get
3x^2 = 4x-4
The next step is to put everything on the same side of the equation:
3x^2 -4x +4 =4x-4 - 4x+4
You now have 3x^2 -4x +4 =0
Hope this helps